Imaging: Multifunctional Biomedical Imaging in Physiological and Pathological Conditions Using a NIR‐II Probe (Adv. Funct. Mater. 23/2017). (June 2017) - Shou, Kangquan; Qu, Chunrong; Sun, Yao; Chen, Hao; Chen, Si; Zhang, Lei; Xu, Haibo; Hong, Xuechuan; Yu, Aixi; Cheng, Zhen
Abstract : In article number1700995, Aixi Yu, Zhen Cheng, and co‐workers describe the creation of highly biocompatible, small‐organic‐molecules‐based nano‐vesicles with fluorescent emission in the NIR‐II window. This imaging agent can noninvasively and dynamically visualize many physiological and pathological conditions, and aid surgeons in performing accurate surgery. This approach will enable better diseases diagnosis and treatment in the era of precision medicine.